Toward an automated workflow for the study of plasma protein-drug interactions based on capillary electrophoresis-frontal analysis combined with in-capillary mixing of interacting partners - Michalcová, Lenka; Nevídalová, Hana; Glatz, Zdeněk (Journal of chromatography. A, Including electrophoresis and other separation methods, 2021)
Capillary electrophoresis-frontal analysis (CE-FA) together with mobility shift affinity CE is the most frequently used mode of affinity CE for a study of plasma protein-drug interactions, which is a substantial part of the early stage of drug discovery. Whereas in the classic CE-FA setup the sample is prepared by off-line mixing of the interaction partners in the sample vial outside the CE instrument and after a short incubation period loaded into the capillary and analysed, in this work a new methodological approach has been developed that combines CE-FA with the mixing of interacting partners directly inside the capillary. This combination gives rise to a fully automated and versatile methodology for the characterization of these binding interactions besides a substantial reduction in the amounts of sample compounds used. The minimization of possible experimental errors due to the full involving of sophisticated CE instrument in the injection procedure, mixing and separation instead of manual manipulation is another fundamental benefit. The in-capillary mixing is based on the transverse diffusion of laminar flow profile methodology introduced by Krylov et al. using its multi-zone injection modification presented by Řemínek at al.. Actually, after the method optimization, the alternate introduction of six plugs of drug and six plugs of bovine serum protein in BGE, each injected for 3 s at a pressure of -10 mbar (-1 kPa) into the capillary filled by BGE, was found to be the best injection procedure. The method repeatability calculated as RSDs of plateau highs of bovine serum albumin and propranolol as model sample compounds were better than 3.44 %. Its applicability was finally demonstrated on the determination of apparent binding parameters of bovine serum albumin for basic drugs propranolol and lidocaine and acid drug phenylbutazone. The values obtained by a new on-line CE-FA methodology are in agreement with values estimated by classic off-line CE-FA, as well as with literature data obtained using different techniques.
Keywords: elektroforéza kapilární; sérový albumin hovězí; farmaceutická chemie; difuze; Blood Proteins; Chemistry, Pharmaceutical; léčivé přípravky; Propranolol; krevní proteiny; Serum Albumin, Bovine; Diffusion; propranolol; průběh práce; Pharmaceutical Preparations; Workflow; Electrophoresis, Capillary